ECATERINA BALICA, Trends of Violent Criminality in Rural Community. Public Perception and Assessment - DAN BANCIU (Revista Română de Sociologie, 2009)
Violent criminality is a serious social problem which affects social relations, causing numerous victims and prejudices and generating feelings of fear and social insecurity. This study tries to capture the post 1989 evolution of this type of criminality in the rural environment, as well as the reaction of the public in this environment with respect to the phenomenon of violence.